KEABSAHAN KETERANGAN AHLI DALAM TINDAK PIDANA KORUPSI - Erwin Ubwarin (SASI, 2014)
Proof needed to convince the judge that there has been a criminal offense, after HIR to the Code of Criminal Procedure (Criminal Procedure Code) was added Specification Expert as a form of evidence, in the Corruption MCK Ambon City in 2012, the Prosecutor requested an expert witness of the National Association of Indonesian Consultants (NAIC) Mollucas, to perform calculations MCK building construction Ambon, at the hearing the expert testimony submitted evidently not in accordance with skills, whereas in providing expert testimony at both the investigation and the court should have the skills to enter. The results showed that specification experts given for criminal acts that occure and seek state losses in the corruption of Crime MCK Ambon City, but it turns out experts who testified in the investigation process does not have a certification as a construction expert, and he was not breathing sworn. In the process of the corruption court, the public prosecutor can not bring experts from NAIC Mollucas, and testimony just recited, this shows that the expert testimony can not be used or invalid